Identification and characterization of a novel short-type peptidoglycan recognition protein in Apostichopus japonicus. Issue 99 (April 2020) - Hu, Zhenguo; Cao, Xuebin; Guo, Ming; Li, Chenghua
Abstract: Peptidoglycan recognition proteins (PGRPs) are pattern recognition molecules of the innate immune system via specific recognizing peptidoglycan, a unique component of bacterial cell wall. In the present study, a homologous gene encoding PGRP-S was identified and characterized from Apostichopus japonicus and designated as AjPGRP-S . The open reading frame of AjPGRP-S is 756 bp encoding a polypeptide of 251 amino acids (aa) with a signal peptide (1–24 aa) and a typical PGRP domain (37–178 aa). Phylogenetic analysis and sequence alignment revealed that AjPGRP-S is a member of the PGRP-S family. In healthy sea cucumbers, AjPGRP-S was expressed in all examined tissues with the highest distribution in body wall, muscle, and intestine. In Vibrio splendidus -infected sea cucumbers, AjPGRP-S was remarkably induced in coelomocytes. The recombinant AjPGRP-S ( rAjPGRP-S ) was shown to possess the highly amidase activity in the presence of Zn 2+ . Moreover, rAjPGRP-S exhibited agglutination abilities and strong bacteriostatic activities against V. splendidus, V. harveyi, V. parahaemolyticus, Staphylococcus aureus, and Micrococcus luteus . Furthermore, the agglutination ability can be enhanced in the presence of Zn 2+ . In conclusion, our results suggested that AjPGRP-S serves as a pattern recognition molecule involved in the immune response towards various pathogenic infections. Highlights: Complete cDNA sequence of S-type PGRP was identified in Apostichopus japonicus. Vibrio splendidus challenge could significantly induce AjPGRP-S mRNA expression. RAjPGRP-S was shown to possess the highly amidase activity in the presence of Zn 2+ . RAjPGRP-S displayed both the agglutination abilities and bacteriostatic activities against examined bacteria.